Catalytic effects of inherent AAEM on char gasification: A mechanism study using in-situ Raman. (1st January 2022) - Yu, Junqin; Xia, Weidong; Areeprasert, Chinnathan; Ding, Lu; Umeki, Kentaro; Yu, Guangsuo
Abstract: Despite a small proportion of mineral in coal, inherent alkali and alkaline earth metals (AAEM) catalytically affected thermal conversion of coal. The gasification of raw and leached coal char was investigated by using an operando microscopic Raman spectroscopy to explore the effect of content and chemical form of the inherent AAEM on morphology and carbon structure evolution of a single particle during in-situ char gasification. The removal of water-soluble and ion-exchangeable AAEM reduced the R 0.5 of SF, NM and YN char by 53.31%, 49.09% and 35.02%, respectively. As a result, the shrinkage of leached coal char progressed slower than that of the raw coal char. Besides, both water-soluble and ion-exchangeable AAEM accelerated char gasification because of an inhibition of the orderly evolution of carbon structure. Higher gasification temperature weakened the catalytic performance of ion-exchangeable AAEM. With the consumption of carbon, carbon microcrystalline structure of the residual char tended to be ordered, which led to a decrease in active free carbon sites for gasification reaction. Kinetic analysis indicated both water-soluble and ion-exchangeable AAEM reduced the activation energy of SF, NM and YN char by 20.97, 20.82 and 9.38 kJ∙mol −1, respectively, and the effect of ion-exchangeable AAEM was more significant. Highlights: Coupling in-situ analysis of particle shrinkage and carbon structure was conduct. Water-soluble AAEM had more significant effects on carbon structure evolution. Catalytic performance of ion-exchangeable AAEM was better. Evolution of carbon structure affected catalytic mechanism of AAEM.